MicroRNA Expression Patterns of the Kidney in Hyperuricemia Mice Treated with Xiezhuo Chubi Decoction（泄浊除痹方） - 孙维峰 张娴娴 孙奋勇 徐伟 梁静 冯书梅 王天 (Chinese journal of integrative medicine, 2011)
Objective：To investigate the effects of Xiezhuo Chubi Decoction（泄浊除痹方,XZCBD） on the microRNA expression patterns of kidney in mice with hyperuricemia.Methods：Sixty Kunming male mice were randomly divided into the high-,medium-,and low-dose XZCBD groups,benzbromarone group,model group, and control group.Except the control group,all mice were established with yeast method combined with uricase inhibition method to build hyperuricemia model,and the corresponding drugs（37.5 g/kg,18.75 g/kg,9.375 g/kg, and 0.02 g/kg per day） were administrated on the 7th day.On the 22nd day,the blood uric acid concentration was detected,and microRNA with obvious changes in kidney was screened with qRT-PCR.Results：The uric acid in the model group was higher than that in the control group,and the levels of the uric acid were reduced after being treated with XZCBD; the differences among groups were significant（P〈0.05）.Compared with the control group,32 kinds of microRNA expression changes were detected on the 15th day after being treated with high-dose XZCBD by microRNA expression profile screening.Among them,miR-34a could inhibit the expression of human urate anion exthanger 1,and miR-146a might have inhibited the inflammatory reaction.Conclusion： XZCBD could significantly reduce the serum uric acid level; its effect on hyperuricemia might be through affecting microRNA expressions.